Dispensing Antiretrovirals During Covid-19 Lockdown: Pathways to Health System Resilience in Uganda - Zakumumpa, Henry; Tumwine, Christopher; Milliam, Kiconco; Spicer, Neil (Research Square, 2021)
Although there is an emerging evidence base on the impact of Covid-19 pandemic on access to health services in low-and middle-income countries, the related notion of health system resilience has received little empirical attention. The objective of this study was to explore health system resilience at the subnational level in Uganda with regard to strategies for dispensing of antiretrovirals during Covid-19 lockdown restrictions. METHODS We conducted a qualitative case-study of eight districts from Eastern Uganda (Mbale, Sironko, Manafwa, Bulambuli, Bududa) and Western Uganda (Kabarole, Kyegegwa, Kyenjonjo) purposively selected due to having a relatively high HIV burden. Between June and September 2020, we conducted key informant interviews with district health team leaders (n=9), with ART clinic managers (n=36), representatives of PEPFAR implementing organizations (n=6) and six focus group discussions with recipients of HIV/AIDS care (48 participants). Qualitative data were analyzed using thematic approach. RESULTS Five broad strategies for distributing antiretrovirals during ‘lockdown’ emerged in our analysis: accelerating home-based antiretroviral therapy (ART) deliveries,; extending multi-month dispensing from three to six months for stable patients; leveraging the Community Drug Distribution Points (CDDPs) model for ART refill pick-ups at outreach sites in the community; an increased reliance on health information systems, including geospatial technologies, to support ART refill distribution in unmapped rural settings. District health teams reported benefiting from the Covid-19 outbreak response funding to deliver ART refills to homesteads in rural communities. CONCLUSION Although Covid-19 ‘lockdown’ undoubtedly impeded access to facility-based HIV services, it unraveled new possibilities and innovations in the distribution of antiretrovirals in the predominantly rural settings of our case-study districts. Further research is recommended to evaluate the potential of home-based deliveries as an alternative differentiated ART delivery model in Uganda and other countries with a high HIV burden.
Keywords: Covid-19 pandemic; Health services; Lockdown restrictions; health system resilience